Near-infrared fluorescence guided surgery: State of the evidence from a health technology assessment perspective - Géczi, Tibor; Simonka, Zsolt; Lantos, Judit; Wetzel, Melinda; Szabó, Zsolt; Lázár, György; Furák, József (Frontiers in Surgery, 2022)
Different applications of near-infrared fluorescence-guided surgery are very promising, and techniques that help surgeons in intraoperative guidance have been developed, thereby bridging the gap between preoperative imaging and intraoperative visualization and palpation. Thus, these techniques are advantageous in terms of being faster, safer, less invasive, and cheaper. There are a few fluorescent dyes available, but the most commonly used dye is indocyanine green. It can be used in its natural form, but different nanocapsulated and targeted modifications are possible, making this dye more stable and specific. A new active tumor-targeting strategy is the conjugation of indocyanine green nanoparticles with antibodies, making this dye targeted and highly selective to various tumor cells and proteins. In this review, we discuss the application of near-infrared fluorescence-guided techniques in thoracic surgery. During lung surgery, it can help find small, non-palpable, or additional tumor nodules, which is useful for finding the sentinel lymph node and identifying the proper intersegmental plane for segmentectomies. Furthermore, it can help visualize the thoracic duct, smaller bullae of the lung, phrenic nerve, or pleural nodules. We summarize current applications and provide a framework for future applications and development.